Intellectual Property Rights and the Margins of Firm Imports in China. Issue 1 (2nd January 2020) - Wei, Hao; Lian, Huijun
ABSTRACT: We have analyzed the channels through which intellectual property rights (IPRs) affect firms' imports, combined Chinese Customs Database with the Annual Survey of Industrial Firms, and then empirically analyzed the effects of IPRs protection on firms' total imports and margins of imports. We have found that strengthening IPRs protection by raising the product extensive margin significantly increases the import value of Chinese industrial firms. IPRs protection has a larger promoting effect on the import value in areas with a stronger threat of imitation; when a firm's innovation activity becomes more active, IPRs will have a lower promoting effect on the import value.